Effects of paeonol on proliferation and collagen synthesis of rat cardiac fibroblasts induced by aldosterone (Bangladesh Journal of Pharmacology, 2021)
The aim of this study was to explore the possible molecular mechanisms of paeonol in preventing ventricular remodeling. The cell viability of neonatal rat cardiac fibroblasts was detected by the method of MTT. RT-PCR and Western blot were used to measure the expression of TGF-β1, type I collagen and type III collagen. After treating the cardiac fibroblasts with paeonol, the cell viability decreased (p